Analisis Aturan dan Perlindungan Terhadap Bebasnya Keberangkatan dan Kepulangan Pekerja Migran Indonesia (PMI) di Kepulauan Riau - Desi Natalia Putri; Heni Novita; Nisa Aisyah; Sehan Amanda; Vara Diva Enjellina (Jurnal Hukum dan Sosial Politik, 2025)
This study aims to analyze the regulations and legal protections for Indonesian Migrant Workers (PMI) who enter and exit through the Riau Islands, one of the main transit points for labor migration in Indonesia. Although the Indonesian government has enacted Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, its implementation continues to face numerous challenges, including weak supervision, lack of public education for prospective migrants, and the widespread practice of non-procedural placements through unlicensed brokers and rogue agents. Using a qualitative descriptive method with interviews, literature review, and documentation techniques, this research reveals that inefficiencies in the legal system and poor inter-agency coordination have created legal loopholes that compromise the safety and rights of migrant workers. Additionally, domestic economic hardship drives many individuals to pursue informal migration routes despite the high risks. This study highlights the urgency of strengthening legal protection mechanisms, simplifying legal migration processes, and improving public awareness to reduce illegal departures and enhance the protection of Indonesian migrant workers abroad.